John Barth literary manuscripts - Barth, John, 1930-; Barth, John, 1930-; Barth, John, 1930-; Barth, John, 1930-; Barth, John, 1930-
Holograph drafts, annotated typewritten manuscripts, corrected galley and foundry proofs, and miscellaneous editorial material from four of Barth's novels: The Floating Opera (1955), The End of the Road (1958), The Sot-Weed Factor (1960), and Giles Goat-Boy; or, The Revised New Syllabus (1966). Also includes manuscripts of several of Barth's short stories, nonfiction essays, and speeches. Among the speeches are drafts of "Jorge Luis Borges and the Literature of Exhaustion" that Barth delivered at various universities in 1966 prior to the publication of his essay "The Literature of Exhaustion" in 1967.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Borges, Jorge Luis, -- 1899-1986.; American essays; American fiction; American literature; Short stories; Speeches, addresses, etc; Authors